Looking for dementia friendly communities: towards an interdisciplinary understanding using a case study, fragments and cut-ups - Aelwyn Williams (2022)
This thesis tries to develop an understanding of the phenomenon of ‘Dementia Friendly Communities’ (DFCs), a policy initiative which has been pursued during the last decade in the nations and regions of the UK, and other parts of the world. In Wales, this has coincided with a radical shrinking of state budgets to deliver social care support, often called ‘austerity’, and rising interest in the policy and cultural implications of an ageing society, and how dementia has seemingly become more central in that demographic trend. This inquiry arises initially from a critical gerontology perspective but develops along lines which borrow from cultural geography and post-war, avantgarde literature. Such an interdisciplinary approach presents opportunities for using novel methods of collecting and analysing material. Though conventional ethnographic techniques such as participant observation, interviewing and photography were used throughout, I also introduce practises such as writing using spontaneous prose, collaging or cut-ups, as an alternative means of analysis. During fieldwork, I attended various events and meetings with those involved in developing DFCs, including ‘dementia activists’, and witnessed the development of ‘Meeting Centres’ as a chosen approach to support those with dementias and their carers in the market town of Brecon, south Wales. From this, a picture emerges of a phenomenon which seems contingent and difficult to grasp, but offers space for critical counter-conducts, glimpses of community-making and types of citizenship. Foucauldian concepts such as biopolitics, governmentality and pastoral power, alongside more non-representational and affective approaches, were used throughout. Writers such as William S. Burroughs, Georges Perec and others inspired ‘ways of doing and making that [could] intervene in the general distribution of ways of doing and making’ (Rancière, 2004, p13). Findings are presented as a series of fragments, including fictocritical and anecdotal writing, collages and cut-ups of materials generated. The main contribution of this study is to attempt to a more nuanced portrayal of DFCs as found, whilst developing methods which question epistemic boundaries, and may have practical potential for synthesising new materials across disciplinary borders.